Secured web-based video repository for multicenter studies. Issue 4 (April 2015) - Yan, Ling; Hicks, Matt; Winslow, Korey; Comella, Cynthia; Ludlow, Christy; Jinnah, H.A.; Rosen, Ami R.; Wright, Laura; Galpern, Wendy R.; Perlmutter, Joel S.
Abstract: Background: We developed a novel secured web-based dystonia video repository for the Dystonia Coalition, part of the Rare Disease Clinical Research network funded by the Office of Rare Diseases Research and the National Institute of Neurological Disorders and Stroke. A critical component of phenotypic data collection for all projects of the Dystonia Coalition includes a standardized video of each participant. We now describe our method for collecting, serving and securing these videos that is widely applicable to other studies. Methods: Each recruiting site uploads standardized videos to a centralized secured server for processing to permit website posting. The streaming technology used to view the videos from the website does not allow downloading of video files. With appropriate institutional review board approval and agreement with the hosting institution, users can search and view selected videos on the website using customizable, permissions-based access that maintains security yet facilitates research and quality control. Results: This approach provides a convenient platform for researchers across institutions to evaluate and analyze shared video data. We have applied this methodology for quality control, confirmation of diagnoses, validation of rating scales, and implementation of new research projects. Conclusions: We believe our system can be a model for similar projects that require access to common video resources. Highlights: Development of a secured video repository that permits permission-based access. Prevents direct file download of videos. Development of broad-based video protocol for patients with dystonia or any movement disorder.